Interlanguage and Free Variation: A Case Study - majid amerian (Matn/Pizhūhī-i Adabī, 2006)
This study attempts to investigate the existence of free variation in interlanguage; an issue that is sti11 a controversial debate among researchers in second language acquisition field. The subject, a nineteen• year-old freshman student of 'English language and literature', wrote 217 diaries in two successive terms. The diaries were analyzed and studied regarding the subject's tense development in order to examine the random use of various verb forms. The results revealed a highly systematic variability. The linguistic context as well as the regularity/irregularity of the verb forms and the subject's native language were, among others, the main sources of systematic variability in using various tense forms in her inter language.